Recent Advances in Cryopreservation - Yamashiro, Hideaki (IntechOpen, 2014)
Cryopreservation of germ cells has potential applications not only for production of next generations of animals but also for general reproductive biology including several field of biology. The present book Recent Advances in Cryopreservation is written by scientists from 5 countries in the field of somatic cells, fish, livestock and humans. In the near future, frontiers in cryopreservation will conceptualise new cryobiological ideas and technologies. We hope the book will be interesting to wide audience.